2003
DOI: 10.1007/s00467-003-1207-0
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for steroid-resistant nephrotic syndrome: a systematic review

Abstract: In a systematic review and meta-analysis of randomized controlled trials (RCT), we aimed to evaluate the benefits and harms of all interventions for children with steroid-resistant nephrotic syndrome (SRNS). Nine RCTs involving 225 children were included. Cyclosporin when compared with placebo or no treatment significantly increased the number of children who achieved complete remission [3 trials, 49 children, relative risk (RR) for persistent nephrotic syndrome 0.64, 95% confidence intervals (CI), 0.47-0.88].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
0
32
0
4
Order By: Relevance
“…However, few side-effects were reported in the trials and findings reported differed little between the control and treatment groups. As reported in Habashy and colleagues, 42 this may be due to small patient numbers in the trials, short follow-up periods and incomplete reporting. None of the ciclosporin studies reports data on the side-effects that commonly concern patients and clinicians, namely nephrotoxicity and hirsutism.…”
Section: Adverse Eventsmentioning
confidence: 87%
See 2 more Smart Citations
“…However, few side-effects were reported in the trials and findings reported differed little between the control and treatment groups. As reported in Habashy and colleagues, 42 this may be due to small patient numbers in the trials, short follow-up periods and incomplete reporting. None of the ciclosporin studies reports data on the side-effects that commonly concern patients and clinicians, namely nephrotoxicity and hirsutism.…”
Section: Adverse Eventsmentioning
confidence: 87%
“…In total, 1815 references were identified and, of these, two systematic reviews 40,42 and 11 trials met the inclusion criteria for the review. Six were parallel RCTs, 22,32,[43][44][45][46] three were randomised cross-over trials, 38,41,47 one was a CCT 48 and one was a prospective cohort study with concurrent controls.…”
Section: Quantity and Quality Of Research Availablementioning
confidence: 99%
See 1 more Smart Citation
“…MMF is a promising therapeutic alternative without nephrotoxicity [20]. But there is no single consensus regarding the indications of renal biopsy and treatment protocols in children with SRNS [13,14,15,16]. Optimal combinations of these agents with the least toxicity remain to be determined [12].…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa faktor yang mempermudah anak SN mengalami infeksi kuman adalah rendahnya kadar IgG karena sintesis yang tidak sempurna, lepasnya faktor B dalam urin, dan tidak sempurnanya fungsi limfosit T. Faktor B adalah cofactor dari C3b dalam jalur alternatif dari komplemen, yang berperan penting dalam opsonisasi kuman (23). Disamping itu pengobatan kortikosteroid atau imunosupresif menambah risiko infeksi (24,25).…”
Section: Hasil Penelitianunclassified